2005
DOI: 10.1002/anie.200462250
|View full text |Cite
|
Sign up to set email alerts
|

Hydroamination/Hydrosilylation Sequence Catalyzed by Titanium Complexes

Abstract: A single precatalyst is used for the sequential combination of the Ti‐catalyzed hydroamination of alkynes with the Ti‐catalyzed hydrosilylation of imines. In this way alkynes and primary amines are converted efficiently into secondary amines in a fully catalytic one‐pot process (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Moreover, CGC properties may be exploited in the so-called ''chain-shuttling polymerization'' [103], where two different catalysts that produce different polymer structures are used. In recent years, CGCs have been applied in some organic transformations such as hydroamination [104,105] for the synthesis of imines (using enatiomerically pure amines) [106] or pyrroles [107,108], or even in a one-pot hydroamination/hydrosilylation sequence [109].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CGC properties may be exploited in the so-called ''chain-shuttling polymerization'' [103], where two different catalysts that produce different polymer structures are used. In recent years, CGCs have been applied in some organic transformations such as hydroamination [104,105] for the synthesis of imines (using enatiomerically pure amines) [106] or pyrroles [107,108], or even in a one-pot hydroamination/hydrosilylation sequence [109].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, a report by Doye et al attracted our attention. In this case, a Ti complex functioned as a single catalyst and promoted both hydroamination and hydrosilylation reactions for the addition of terminal alkynes and anilines 6. In a typical reductive hydroamination reaction, the second reduction (hydrogenation) step is generally achieved by using either a separate catalyst system, such as ZnCl 2 /NaBH 3 CN,2a or a strong reducing agent, such as LiAlH 4 7.…”
Section: Introductionmentioning
confidence: 99%
“…45 In titanium series, Doye et al reported a catalysed sequential one pot two step reaction of terminal and internal alkynes with amines. 115 Starting from aniline derivatives and primary alkylamines by reaction with 1-phenylprop-1-yne, various secondary amines were synthesized in poor (6%) to excellent (99%) yields. In a first step, the alkyne, primary amines and Cp 2 TiMe 2 C22b (10 mol%) or the complex C49 (10 mol%) are warmed in toluene at 105 °C for 24 h. Then 3 equiv.…”
Section: Scheme 53 Ir-catalysed Intramolecular Hydroamination/hydrosmentioning
confidence: 99%